Development of Guidelines to Attenuate Galvanic Corrosion between Mechanically-Coupled Aluminum and Carbon-Fiber Reinforced Epoxy Composites Using Insulation Layers. Issue 10 (6th August 2015) - Srinivasan, Raghu; Nelson, Jeffrey A.; Hihara, L. H.
Abstract : The use of an insulating skirt to attenuate galvanic action between mechanically-coupled 6061-T6 aluminum (Al) and electrically conductive carbon fiber reinforced (CFR) polymer-matrix composites (PMCs) was assessed, analyzed and modeled. The galvanic-corrosion current as a function of time between the 6061-T6 Al and CFR PMCs for a range of insulative skirt lengths, ls, and sodium chloride (NaCl) salt loadings, m ′, in a humidity chamber at 30°C and 90% relative humidity (RH) were monitored. Polarization experiments were conducted on 6061-T6 Al and conductive CFR PMC electrodes to study the mechanisms governing galvanic corrosion in solutions ranging from 0 ppm chloride (Cl − ) to 20, 000 ppm Cl − concentrations. Based on the electrochemical characteristics of Al and the CFR PMC and the ohmic loss within the galvanic couple, a model was developed that related the galvanic corrosion rate ( iGalv ) to the value of ls / m ′, which is the ratio of the insulating skirt length to salt loading. Experimental data from the polarization experiments as well as data from monitoring the galvanic couples in the humidity-chamber galvanic experiments were used to generate plots of log ls / m ′ vs log iGalv, which can be used in design to determine proper skirt length for various environments (based on salt-loading levels) to limit the galvanic corrosion rate to a specified value.